Ballistic behavior and microstructure evolution of B4C/AA2024 composites. Issue 16 (November 2019) - Chao, Z.L.; Sun, T.T.; Jiang, L.T.; Zhou, Z.S.; Chen, G.Q.; Q.Z,; Wu, G.H.
Abstract: In this research, the ballistic behavior and microstructure evolution of 45vol% B4 C/AA2024 composites produced by pressure infiltration method were studied. The ballistic behavior of composites was carried out using 7.62 mm armor-piercing incendiary (API). The results demonstrate that the 45vol% B4 C/AA2024 composites has excellent ballistic performance and the protection coefficient reaches 3.6. The residual microstructure of composites after impact was mainly investigated by the transmission electron microscope (TEM). The results show that the residual microstructure of B4 C particles mainly include dislocations, stacking faults, twins and poly-crystallization. For Al matrix, the residual microstructure is mainly the existence of large numbers of dislocations especially in the area near the sharp corner of B4 C particles. In addition, inhomogeneous precipitates of AA2024 matrix were observed after impact.